Meghāṇī - Meghāṇī, Mahendra (Lokamilāpa Ṭrasṭa, 2008)
Reminiscences about Zaverchand Kalidas Meghani, 1896-1947, Gujarati author; includes three of his autobiographical writings
In Gujarati-Schr
Keywords: Autobiografie; Meghani; Zaverchand Kalidas 1896-1947; Authors; Gujarati